2022
DOI: 10.3329/sja.v19i2.57668
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanotechnology in Insect Pest Management: A Review

Abstract: Insect pests are one of the most concerned biotic obstacles in agriculture and humans are constantly in search of new strategies to control them. Chemical pesticides are extensively used for controlling insect pests which cause a lot of problem, such as pest resistance, elimination of natural enemies, environmental pollution, loss of biodiversity and human health hazards. As an alternative pest control strategy, the application of nanotechnology in insect pest management can be one of the most promising ways t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…Note that the recorded fact distinguishes whiteflies as their tolerance and resistance to many chemical pesticides, so the Nanopesticide can be considered very effective and it is recommended to use it to combat this pest. This results identical to [6][3] were founded whiteflies have the ability to develop resistance to both conventional and nonconventional insecticides. Through the results obtained, the nanoparticles from the aqueous extract of naringin (Citrus aurantium) showed a very high significant effect in the mortality rate of the mosquitoes of the third and fourth stages and the virgin in vitro; in addition to its significant effect on the mortality rates of the white fly stages in the laboratory and in the field.…”
Section: 10nanoparticle Efficiencysupporting
confidence: 77%
See 2 more Smart Citations
“…Note that the recorded fact distinguishes whiteflies as their tolerance and resistance to many chemical pesticides, so the Nanopesticide can be considered very effective and it is recommended to use it to combat this pest. This results identical to [6][3] were founded whiteflies have the ability to develop resistance to both conventional and nonconventional insecticides. Through the results obtained, the nanoparticles from the aqueous extract of naringin (Citrus aurantium) showed a very high significant effect in the mortality rate of the mosquitoes of the third and fourth stages and the virgin in vitro; in addition to its significant effect on the mortality rates of the white fly stages in the laboratory and in the field.…”
Section: 10nanoparticle Efficiencysupporting
confidence: 77%
“…Five eggplant seedlings were purchased in pots and placed inside breeding houses covered from the outside with a dull cloth. Seven pairs of whitefly's adults were released into each cage for the insect brought from greenhouses and from both sexes and after 24 hours of laying eggs, the eggs were isolated for each seedling, with the same the method for nymphs, replicates (eggs, nymphs) were treated, duplicates were treated with the prepared pesticide by sprinkler, and the killing numbers readings were taken and recorded after 24, 48, and 72 hours, and the percentage of pesticide efficacy was calculated using the percentage killing percentage according to Abbot's formula [6], after which the percentage of the killed percentage was converted into proportions Angle according to and then subjected to statistical analysis [22] (1)…”
Section: Breeding Whitefly Bemisia Tabacimentioning
confidence: 99%
See 1 more Smart Citation
“…One area where nanotechnology has shown promise is in improving regulated ecological life support systems. This has been highlighted in several recent studies, including those conducted by Zannat R et al (2021) [ 22 ], [ 23 ], and [ 24 ]. These studies have demonstrated the potential of nanotechnology to enhance the efficiency and effectiveness of ecological life support systems, thereby contributing to the sustainable development of our planet.…”
Section: Introductionmentioning
confidence: 94%
“…113 The agricultural application of nanotechnology extends to the development of efficient formulations including pesticides, insecticides, insect repellents and pheromones. 107,114,115 Global scenario of nano-bioinsecticides Scientific research facilities and leading agrochemical producers (such as Novartis AG, Bayer, BASF, Indigo, Symrise, Monsanto, Dow AgroSciences, and Syngenta) have consistently endeavoured to develop nanoinsecticides, with many of these formulations being subject to patents. In the last 20 years, more than 3600 nanoformulation insecticides have been granted patents.…”
Section: Nanotechnology Tools For Pest Management In Agriculturementioning
confidence: 99%